KEBIJAKAN EKSPOR PASIR LAUT TERHADAP ANCAMAN PERTAHANAN KEAMANAN NEGARA - mirozul, aldy; Irwan Triadi (Al Qisthas Jurnal Hukum dan Politik, 2023)
The policy of utilizing marine sedimentation, one of which is the export of sea sand, has reappeared in Government Regulation Number 26 of 2023 concerning the Management of Sedimentation Products in the Sea. This government regulation on the utilization of sedimentation results in the form of sea sand and other sedimentary materials in the form of mud used for reclamation, government infrastructure development, infrastructure development by business actors and exports as long as domestic needs are met. Normative legal research or library legal research, with a statutory regulation approach. The nature of this research is normative juridical because the researcher will carry out an analysis of the regulations regarding the use of sedimentation with other laws and regulations. The results of research on the policy for implementing sea sand exports as stated in Government Regulation Number 26 of 2023 concerning Management of Sedimentation Products in the Sea has the potential to cause marine environmental problems and impact the loss of small islands which indirectly threatens the defense and security of the Indonesian state